The Internship Awakening: Work-Based Learning at CSU Dominguez Hills. - Castillo, Karla; Alvarez, Natalie; Lepe, Linda; Martinez, Damian (Experiential Learning and Teaching in Higher Education, 2025)
A lighter look at some of the socioeconomic and emotional hurdles students face when they consider internships -- and how educators can help. Meet Karla Castillo, Director of Work Based Learning program at the College of Health, Human Services & Nursing, and three peer leaders of the Toro Health Pathways.